6x+13=35-3x

Simple and best practice solution for 6x+13=35-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+13=35-3x equation:


Simplifying
6x + 13 = 35 + -3x

Reorder the terms:
13 + 6x = 35 + -3x

Solving
13 + 6x = 35 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
13 + 6x + 3x = 35 + -3x + 3x

Combine like terms: 6x + 3x = 9x
13 + 9x = 35 + -3x + 3x

Combine like terms: -3x + 3x = 0
13 + 9x = 35 + 0
13 + 9x = 35

Add '-13' to each side of the equation.
13 + -13 + 9x = 35 + -13

Combine like terms: 13 + -13 = 0
0 + 9x = 35 + -13
9x = 35 + -13

Combine like terms: 35 + -13 = 22
9x = 22

Divide each side by '9'.
x = 2.444444444

Simplifying
x = 2.444444444

See similar equations:

| (3d+2)(7-1)=0 | | -4x-10=46+5x | | (1/3x)=9 | | 4x+1=60 | | 5x-16=4x+5 | | x-10=-21+2x | | x^2=5+4x | | x+7=-0 | | 5+7=3x | | x^2=y^4-77 | | y=5-8x | | 12x-10=4x-5 | | 2x+3=33+7x | | (-3y^2-8y)+(6y^2+y-9)= | | 18(4/9) | | -4/7+2/5u=-1/2 | | -4+7x=x+20 | | 9x+6=3x-2 | | 5(8)+8y=40 | | x*x+6x+c= | | 6y^2+11=4y | | 10/15x=8 | | X/8=x+3/20 | | 5+2n=31 | | m^2-54=3m | | 3-3x=5x-85 | | 20/10x | | 4x^3-5x+5=0 | | y^2=14-5y | | x=14+3 | | 6x+9=7x+5 | | -2a(a+3)= |

Equations solver categories